Indigenous People and The Sustainable Development Goals in Brazil: A Study of the Kaingang People. Issue 4 (December 2020) - Renwick, Neil; Reid, Darren R.; Santos, Jorge Alejandro; Piovezana, Leonel
Indigenous Peoples continue to face substantial challenges. This article focuses on the Kaingang People in Southern Brazil and is contextualized by the Sustainable Development Goals (SDG) adopted by all the United Nations member states in 2015. The authors adopted an Indigenist research methodology to obtain oral evidence and provided an education-focused case-study. The research findings reveal that, despite Brazilian Constitutional recognition and SDG provisions, in practice, the Indigenous People in Brazil are experiencing renewed threats to their indigeneity. The SDGs need to be implemented more robustly at the local level to overcome these emancipatory barriers. The article reveals the key role of empowerment that can be played by carefully articulated indigenous education programs.